Context of knowledge and network capabilities: a framework for achieving innovation strategies for SMEs in Bandung City - Ahmad Johan Johan; Ratih Hurriyati; Puspo Dewi Dirgantara (Manajemen dan Bisnis, 2022)
Small and medium enterprises in Indonesia are currently facing stiff competition because more and more competitors are emerging. To win the competition, local companies must pay attention to the strategies adopted so as to produce innovations that can be a strength for the organization itself. Factors that influence the creation of innovation it self include knowledge management and network capability. The purpose of this study is to investigate how knowledge management and network capability affect the creation of innovation. This research uses descriptive research. Data was collected through a survey by distributing questionnaires to 200 respondents and returning 170 respondents. The results of the study indicate that there is a positive influence between knowledge management on network capability and the creation of innovation, besides that network capability has a significant effect on the creation of innovation.